Implementation of Policy Based Route and Failover with Netwatch Using Mikrotik Router on PT. Len Industrial - Oki Sudi Wijaya, Werry; Rizal, Syahril; Suryayusra, Suryayusra; Irawan, Dedi (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
Computer networks have now become a primary need for some people, be it to do work or other things. The same happened at the site office of PT. LEN Industri Palembang all employees are very dependent on public network connections or the internet to do work or communicate with sites or head offices. Sometimes the network is disrupted so that it does not allow employees to do their work. Therefore, researchers will implement policy-based route based failover which aims to separate traffic and also failover as a backup connection, this can be implemented using a built-in tool from MikroTik, namely Netwatch and also 2 ISPs that work in a way when ISP 1 experiences interference, traffic will be diverted to ISP 2 or vice versa and by using policy based route traffic on the network can be separated so that it is not Make the network choked or full traffic.